Detection of Quorum Sensing Signal Molecules and Identification of an Autoinducer Synthase Gene among Biofilm Forming Clinical Isolates of Acinetobacter spp. - Anbazhagan, Deepa; Mansor, Marzida; Ong, Gracie Siok Yan; Yusof, Mohd Yasim Mohd; Hassan, Hamimah; Sekaran, Shamala Devi (Public Library of Science, 2012)
Background: Quorum sensing is a term that describes an environmental sensing system that allows bacteria to monitor their own population density which contributes significantly to the size and development of the biofilm. Many gram negative bacteria use N-acyl-homoserine lactones as quorum sensing signal molecules. In this study, we sought to find out if the biofilm formation among clinical isolates of Acinetobacter spp. is under the control of autoinducing quorum sensing molecules.